The status of ethics in Swedish health care management: a qualitative study - Anna T. Höglund; Erica Falkenström (BMC, 2018)
Abstract Background By tradition, the Swedish health care system is based on a representative and parliamentary form of government. Recently, new management forms, inspired by market principles, have developed. The steering system is both national and regional, in that self-governing county councils are responsible for the financing and provision of health care in different regions. National and local documents regulating Swedish health care mention several ethical values, such as equity in health for the whole population and respect for autonomy and human dignity. It is therefore of interest to investigate the status of such ethical statements in Swedish health care management. Method The aim of the present study was to investigate perceptions of the status of ethics in the daily work of politicians, chief civil servants and Chief Executive Officers (CEOs) from care-giver organizations in the county council of Stockholm. A qualitative method was used, based on inductive content analysis of individual interviews with 13 health care managers. Results The content analysis resulted in four categories: Low status of ethics; Cost-effectiveness over ethics; Separation of ethics from management; and Lack of opportunities for ethical competence building. The informants described how they prioritized economic concerns over ethics and separated ethics from their daily work. They also expressed that they experienced that this development had been enforced by the marketization of the health care system. Further, they described how they lacked opportunities for ethical discussions, which could have helped develop their ethical competence. Conclusions In order to improve the status of ethics in health care management, ethical considerations and analyses must be integrated in the regular work tasks of politicians, chief civil servants and CEOs; such as decision-making, budgeting and reform work. Further, opportunities for ethical dialogues on a regular basis should be organized, in order to improve ethical competence on the management level. New steering forms, less focused upon market principles, might also be needed, in order to improve the status of ethics in the health care management organization.